IMPROVING PRODUCTIVITY THROUGH EVALUATION AND IMPROVEMENT OF SETUP TIME ON PIPE LASER CUTTING MACHINE USING SINGLE MINUTE EXCHANGE OF DIE (SMED) METHOD - Pangastuti, Nova; Parningotan, Sepriandi (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to improve setup time efficiency on a pipe laser cutting machine using the Single Minute Exchange of Die (SMED) method. Initial identification includes an analysis of the machine setup time by taking into account the Rating Factor and operator allowance. The normal setup time is 2,936.64 seconds, with an operator rating factor of 0.14. The conversion from internal to external setup resulted in a 16% decrease in setup time, but the initial improvement was not significant. Through fishbone analysis, the factors causing the high setup time were identified, and improvement solutions were proposed for management, equipment, environment, materials, machines, and methods. The second improvement was made by replacing problematic bolts, resulting in a 30% decrease in setup time. The application of SMED proved to increase process time efficiency by 30%, potentially increasing the company's productivity in pipe machining.